Quality of Financial Statement: The Influence of Regional Government Information Systems, Regional Financial Accounting Systems, Apparatus Competence - Iska Herdiana; Rahma Masdar; Betty Betty; Muhammad Din; Jamaluddin Jamaluddin (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This research paper investigates the relationship between apparatus competency, the regional financial accounting system, the regional government information system, and financial statement quality. In the present research, a quantitative technique and purposive sampling are used. The data gathered via questionnaires were analyzed using IBM SPSS 27. The outcome demonstrates that the regional government information system has no effect on the quality of financial statements. On the other hand, the regional financial accounting system and apparatus competency have a substantial impact on the financial statement quality. The conclusions imply that the presence of an information system, the ability of the apparatus to manage regional finances, and the execution of a sound accounting system all affect the financial statement quality. Therefore, in order to produce financial statements that are more transparent, accountable, and of higher quality, local governments must improve the quality of regional government information system implementation, strengthen the practice of regional financial accounting systems, and continuously improve the skills of officials.